The Pattern of Acute Poisoning in Children in Chudary Mohammad Akram Teaching and Research Hospital Lahore - Nosheen Iftikhar, Imran Abbas, Shabir Ahmed, Waheed Ahmad, Nayyab Butt, Allah Nawaz Sultan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Acute poisoning is one of the identifiable cause of morbidity and death in children less than five years of age. The type of substance taken and prevalence vary from place to place and over time. Aim: To assess the frequency and pattern of acute poisoning in children in Chaudhry Muhammad Akram Teaching and Research Hospital, Lahore. Methods: This retrospective study was conducted at the Pediatrics Emergency of Chaudhry Muhammad Akram Hospital from July 2017 to June 2019 (2 year). All cases of acute poisoning in children that presented within that period were reviewed and important information extracted by retrieving data from hospital records and patients files. Results: One hundred children were referred to pediatrics emergency departments of Chaudhry Muhammad Akram Hospital due to acute poisoning. 55(55%) were between 2-5 year of age group, 27(27%) were between 6-10 year of age group and 18(18%) were between 11-14 year old. 60(60%) were male and 40(40%) were female. There was Ingestion of poison in 97(97%) and 3 (3%) had poisoning through skin contamination. The most common poisoning agent was Corrosive 71(71 %), followed by Hydrocarbon 11(11%), Drugs 9(9%), Agrochemical 7(7%), Plants and Insect poisoning 1(1%) respectively. Conclusion: Acute poisoning is a significant cause of morbidity among children in developing countries. Acute poisoning is common in Pakistan, with appreciable mortality, Bleach being the most common agent now a days.